RESOLVING DISPUTES ARISING FROM NFT TRANSACTIONS THROUGH ARBITRATION: AN ANALYSIS FROM THE PERSPECTIVE OF UZBEK CIVIL LAW AND THE NEW YORK CONVENTION (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines the legal problems involved in resolving, through arbitration, disputes arising from transactions with non-fungible tokens (NFTs), viewed from the perspective of the civil legislation of Uzbekistan and the 1958 New York Convention. The article analyzes the distinctive legal and technological features of NFTs—their non-fungibility, the automatic and irreversible execution of smart contracts, the legal separation between the token and the underlying work, the centralized storage of metadata, and the cross-border, pseudonymous nature of the market—and shows how these features complicate evidence-gathering and enforcement in traditional litigation. Particular attention is paid to the question of the legal force of arbitration clauses concluded in electronic form, including through smart contracts and click-through agreements, in light of the requirements of Article II of the New York Convention and the general provisions of the Civil Code of Uzbekistan on freedom of contract and genuine consent. On the basis of comparative experience, in particular U.S. case law on browsewrap and clickwrap agreements, the article proposes concrete legislative and institutional measures for Uzbekistan, including express statutory recognition of electronically concluded arbitration agreements, minimal procedural safeguards confirming informed consent to arbitration clauses, and the development of specialized arbitration capacity for disputes involving digital assets.
Keywords: NFT, smart contract, arbitration agreement, New York Convention, Civil Code of Uzbekistan, alternative dispute resolution.